Mindful Screens: Enhancing Early Childhood Emotional Awareness through Reflective Animation Media - Fairuz Annisa; Edi Waluyo; Ali Formen; Diana (Jurnal Pendidikan Anak Usia Dini Undiksha, 2026)
Emotional awareness in early childhood has not yet developed optimally due to the limited availability of structured learning media and the lack of pedagogical support in social-emotional learning. This study aims to analyze and evaluate the effectiveness of mindfulness-based reflective animation in improving children’s ability to recognize, label, and regulate emotions. This study used a mixed methods approach with a quasi-experimental design. The research subjects consisted of 30 children aged 4–6 years who were divided into an experimental group and a control group. Data were collected through structured observation using a validated emotional awareness observation sheet, teacher journals, classroom observations, and post-intervention interviews. Quantitative data were analyzed using statistical tests, while qualitative data were analyzed through thematic analysis. The results showed that children in the experimental group experienced significant improvements in emotion recognition, the use of emotional vocabulary, and self-regulation, whereas the control group showed relatively minimal changes. This study concludes that mindfulness-based reflective animation is an effective, engaging, and developmentally appropriate medium for supporting emotional development. The implications of this study emphasize the importance of integrating culturally responsive digital media and strengthening the role of teachers in social-emotional learning in early childhood education.